Bhopal and the Struggle for Social Justice in India - Kumar, Madhuresh (Social justice, 2014)
The article focuses on the struggle for social justice in India after the 1984 Union Carbide pesticide plant disaster that occurred in Bhopal, India. Topics include social justice within India, corporate accountability for industrial disasters, and the organization of social movements in India. Information is provided on environmental law in India.